PERLINDUNGAN HUKUM TERHADAP HAK BERUNDING PERJANJIAN KERJA BERSAMA SERIKAT PEKERJA YANG TIDAK DIPENUHI OLEH PENGUSAHA - Sopyan Sopyan; Deny Guntara; Muhamad Abas (UNES Law Review, 2023)
The purpose of this writing is to learn how the Collective Labor Agreement (PKB) is governed by law and what legal recourses can be taken against the alleged rejection of the PKB. This examination is an illustrative subjective exploration. The methodology utilized is an exact juridical methodology, in particular breaking down an issue utilizing regulations and guidelines which are then deciphered with experimental information in the field. The method of legal reasoning, which is an activity to find a legal basis contained in a legal event, is the method of data analysis utilized in this study. whether it is a legitimate demonstration or an unlawful demonstration (criminal, common or regulatory) and remember it for the current lawful guidelines. The consequences of this study show that there are charges that businesses with different reasons reject the presence of an Aggregate Work Understanding (PKB) in their organization despite the fact that the circumstances for worker's guilds have been satisfied to apply for the option to arrange. Conflicts with labor unions followed the implementation of the Collective Labor Agreement (PKB). despite the fact that, in accordance with PERMENAKER RI No. Employers are required to serve trade unions and labor unions that submit written requests to negotiate collective labor agreements (PKB) under Section 28 of 2014, which is about the Procedures for Making and Ratifying Company Regulations and Making and Registering Collective Labor Agreements.